Implementation Of Article 240 Paragraph (1) Letters G Act No. 7 Of 2017 In The Making Of Combating Corruption Crime In Legislative Institutions (Case Study in KPU of Central Java) - Nurul Fuji Sri Hastuti; Jawade Hafidz (Jurnal Daulat Hukum, 2019)
This study aims to: 1) identify and explain the implementation of Article 240 paragraph (1) letter g of Act No. 7 of 2017 by the Election Commission of Central Java, and 2) to assess and analyze the implementation of Article 240 paragraph (1) letter g of Act No. 7 of 2017 can realize eradication of corruption. The study used socio-juridical approach method to examine and discuss the issues that was raised, followed by conducting research and interviews in person at the Election Commission of Central Java, Semarang Corruption Court, Academician, Member of Party Politics and Society. As well as the author uses the theory of utilitarianism, to analyze the problem. The results showed: 1) ex-convict corruption are not allowed to run for legislative candidates in accordance with the regulations of PKPU No. 20 of 2018. 2) In Article 240 paragraph (1) letter g Electoral Act No. 7 of 2017 on the content of the article is general in nature so that the sentence can not be accommodated on the eradication of corruption because in the article does not explicitly include the prohibition of ex-convict corruption to be nominated again as legislative candidates. Keywords: Election; Legislative Candidate; Corruption Crime.